If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2x+1)(x-2)=-2
We move all terms to the left:
(2x+1)(x-2)-(-2)=0
We add all the numbers together, and all the variables
(2x+1)(x-2)+2=0
We multiply parentheses ..
(+2x^2-4x+x-2)+2=0
We get rid of parentheses
2x^2-4x+x-2+2=0
We add all the numbers together, and all the variables
2x^2-3x=0
a = 2; b = -3; c = 0;
Δ = b2-4ac
Δ = -32-4·2·0
Δ = 9
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{9}=3$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-3)-3}{2*2}=\frac{0}{4} =0 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-3)+3}{2*2}=\frac{6}{4} =1+1/2 $
| c=8=9 | | 27=w+7 | | 2x-5=x+3=90 | | 6.7+b=4b+4 | | 2.3x+7=-7 | | c=9=8 | | 0.16/0.75=y | | –5+12u+2=–3+12u | | 2.x-7=-7 | | 4x+6=10−3x | | -4x-6=6x-116 | | 1+v=2v+9 | | 6-6x=-25 | | 4x+5-2x+15=110 | | 3/4/1/16=h | | 2x+3x+18=13 | | 9x-73=3x23 | | 5.18-5t+7=(t=3) | | 6x+7x+5x-2x+4x-1=36+7x | | 2x-18=6x-27 | | 4x+5=2x+15=110 | | (12)^5x=(32)^2x-1 | | 10v+1=9v+10 | | 10−7h=–3h+18 | | (x)=0.25x+35 | | 13+7z=7 | | –3t+8=t | | 15x+16=5x+286 | | 80x+0.5=100x | | 16−12x=34x+2 | | 8-9k=-10k-1 | | 5−6k=–5−5k |